Academic Stressors of Junior High School Students (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
Academic stress has been recognized as a prevalent issue among students, potentially affecting their overall wellbeing and academic performance. Understanding the different stressors experienced by the students can be insightful in creating interventions that will enhance their academic achievement. This study was conducted to determine the academic stressors among the respondents. The study employed quantitative descriptive-correlational research design to gather data from 137 randomly selected Junior High School students enrolled at Union Christian College using an adapted questionnaire. The researcher used frequency count and percentage in presenting the profile of the respondents, weighted mean in describing the different academic stressors, and Pearson Product Moment Correlation in the relationship between the variables. The findings revealed that the respondents moderately experience academic stresses related to academic expectations, subject requirements and examinations, and curricular and co-curricular activity. The expectation of their parents contribute to their stress related to academic expectations, while the difficulty of exams and the number of performance tasks they need to require contributes to their stress as to subject requirements and examinations. Meanwhile, they perceive that their participation in school activities is a source of stress as it adds to the required activities they need to comply with. Significant relationship was found between grade level and academic stress related to subject requirements and expectations, implying that the higher the student’s grade level is, the more they experience the burden related to requirements and exams. The results give an insight that the students need to understand how they should manage these stressors to maintain optimal performance in their academics. Thus, the researchers recommend a proposed student-led academic wellness advocacy plan to improve the academic well-being and reduce stress among the students.
Keywords: academic well being; academic stressors; academic performance